Inhibition of Thrombin-Activatable Fibrinolysis Inhibitor and Plasminogen Activator Inhibitor-1 Reduces Ischemic Brain Damage in Mice. Issue 9 (September 2016) - Denorme, Frederik; Wyseure, Tine; Peeters, Miet; Vandeputte, Nele; Gils, Ann; Deckmyn, Hans; Vanhoorelbeke, Karen; Declerck, Paul J.; De Meyer, Simon F.
Abstract : Background and Purpose—: Cerebral ischemia and reperfusion is associated with activation of the coagulation cascade and fibrin deposition in cerebral microvessels. Both thrombin-activatable fibrinolysis inhibitor (TAFI) and plasminogen activator inhibitor-1 (PAI-1) attenuate fibrinolysis and are therefore attractive targets for the treatment of ischemic stroke. Methods—: TAFI and PAI-1 were inhibited by monoclonal antibodies in a mouse model of transient middle cerebral artery occlusion. Twenty-four hours after stroke, mice were neurologically scored, cerebral thrombotic burden was assessed, and brain infarct sizes were calculated. Results—: Inhibition of TAFI or PAI-1 significantly decreased cerebral infarct sizes by 50% 24 hours after stroke. This reduction in cerebral damage was associated with a significant decrease in fibrin(ogen) deposition in the ischemic brain. Concurrently, functional recovery of the animals was improved. Interestingly, combined targeting of TAFI and PAI-1 using low, and by themselves inactive, doses of antibodies improved cerebral blood flow and reduced cerebral fibrin(ogen) deposition and infarct sizes by 50%. When dual treatment was delayed to 1 hour after the start of reperfusion, it still reduced brain injury; however, this was not statistically significant. Conclusions—: Targeting of PAI-1 and TAFI is protective in an ischemic stroke model by attenuating fibrin(ogen) deposition, thereby improving reperfusion. Combined inhibition has a co-operative effect that could become useful in ischemic stroke therapy. Abstract : Supplemental Digital Content is available in the text.